Ser professor em cursos de direito em Fortaleza: visão fenomenológica - Ferreira, Kilvia Souza (2013)
This research study whose purpose is the study of the everyday experience of the ways of being a teacher of Law Courses in Fortaleza, was developed with the intention to reveal this understanding from the speech of teachers in institutions of Public and Private Education. This is a case study in which the predominant online qualitative research, phenomenological approach, based on the main ideas of Edmund Husserl and Martin Heidegger. The origins of law and legal institutions in Brazil, as well as training for law courses. The information was collected in phenomenological interviews, containing guiding questions, which facilitated the emergence of important thematic units to unveil the teacher be inserted in Law Courses in Fortaleza. The analysis sought to identify subthemes revealed his experience in teaching law, which was explained in several reports. The speeches of teachers revealed several aspects regarding your experience in the profession of being a teacher that were grouped into sub-themes, namely - tradition and innovation in the expanded space of the classroom, the modes of teaching and learning in legal spatiality, the understanding of space and environment in which the operator works of law, the need of interdisciplinarity in legal education to understand a complex world, the historicity as a source of legal learning, the importance of the humanities in the legal field, relational modes in space learning, experience and teachings, ways to assess the learning process of the legal field, the change of view about evaluation. With the understanding reached in this study, is expected to raise its daily reflections on teachers, aimed at increasing its role in the current Brazilian legal education. The study provides theoretical contributions to the development of teaching, encouraging thus closer to their experience, essential to reveal the meaning of the phenomenon being a teacher of Law Courses in Fortaleza.